2020
DOI: 10.1007/s11739-020-02362-8
|View full text |Cite
|
Sign up to set email alerts
|

Complicated myocardial infarction in a 99-year-old lady in the era of COVID-19 pandemic: from the need to rule out coronavirus infection to emergency percutaneous coronary angioplasty

Abstract: a 99-year-old woman with hypertension and a previous history of coronary artery disease treated with coronary angioplasty and stent in the proximal left anterior descending coronary artery was admitted to the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…It has been postulated that increased systematic and intraplaque inflammatory activity, persistent destabilization of the plaques, and the prothrombotic and procoagulant state may collectively cause myocardial infarction in these acute respiratory infections 35 . Acute infection triggered myocardial infarction has been observed in COVID-19 patients, especially in severe patients 18 , 36 - 38 . Shi found that 14 out of 416 patients (3.36%) may have developed myocardial ischemia, with features consistent with ST-elevation myocardial infarction 18 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that increased systematic and intraplaque inflammatory activity, persistent destabilization of the plaques, and the prothrombotic and procoagulant state may collectively cause myocardial infarction in these acute respiratory infections 35 . Acute infection triggered myocardial infarction has been observed in COVID-19 patients, especially in severe patients 18 , 36 - 38 . Shi found that 14 out of 416 patients (3.36%) may have developed myocardial ischemia, with features consistent with ST-elevation myocardial infarction 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Complex interactions through direct cardiomyocyte invasion and indirect inflammatory-mediated damage could explain cardiac involvement in COVID-19 [21]. Myocardial injuries have been described in various case reports, from acute myocarditis to pseudo acute myocardial infarction [1][2][3][4]22], and several studies highlight an association between cardiac injuries and mortality [23][24][25][26]. Other studies suggested that abnormal heart rhythms are common [7,13,27].…”
Section: Discussionmentioning
confidence: 99%
“…Emergency units have been early reassessed to identify infected patients and select cases deserving hospitalization or more intensive cares [ 9 ]. Indeed, emergency physicians promptly published their experiences to share the weakness and strength of local organization, with the aim to facilitate other colleagues in different countries [ 10 ]. In accordance with our analysis, a recent bibliometric study also highlighted that the effects of COVID-19 on the healthcare system were the most studied topic (222/481, 46.1%) [ 11 ].…”
mentioning
confidence: 99%